Telaah Segitiga Retorika Aristoteles dalam Video Ceramah Digital - Mohammad Wildan Esra; Aang Ridwan; Umi Halwati (Universitas Muhammadiyah Prof. DR. Hamka, 2026)
The development of digital media has transformed the landscape of Islamic preaching, where religious communicators now deliver messages through platforms such as YouTube. This phenomenon demands persuasive and adaptive communication skills to compete amid information overload. This study aims to analyze the actualization characteristics of ethos, pathos, and logos elements in the digital lectures of Ustadz Muhammad Nuzul Dzikri based on Aristotle's Rhetorical Triangle theory. A qualitative content analysis method with a constructivism paradigm was employed. The data source is a lecture video entitled